Articulating security : the United Nations and its infra-law - Roele, Isobel, 1982- (Cambridge : Cambridge University Press, 2022)
We live in a world of mobile security threats and endemic structural injustice, but the United Nations' go-to solution of strategic management fails to stop threats and perpetuates injustice. Articulating Security is a radical critique of the UN's counter-terrorism strategy. A brilliant new reading of Foucault's concept of disciplinary power and a daring foray into psychoanalysis combine to challenge and redefine how international lawyers talk about security and management. It makes a bold case for the place of law in collective security for, if law is to help tackle injustice in security governance, then it must relinquish its authority and embrace anger. The book sounds an alarm to anyone who assumes law is not implicated in global security, and cautions those who assume that it ought to be.
An articulated security project -- Strategic planning -- Performance review -- Infra-law -- Anti-law -- Uncanny law.
Title from publisher's bibliographic system (viewed on 04 Mar 2022).
Keywords: Foucault, Michel, -- 1926-1984 -- Political and social views; United Nations; Security, International; Terrorism -- Prevention -- Law and legislation; Terrorism (International law)